CONTEXTUAL EFFECT OF COMMUNITY HEALTH SERVICE ON THE USE OF TRIPLE ELIMINATION SERVICE - Verasita, Prissy; Budihastuti, Uki Retno; Murti, Bhisma (Journal of Maternal and Child Health, 2020)
Background: Triple elimination is the elimination of transmission of HIV, syphilis, and hepatitis B from mother to child. The Prevention of Mother to Child Transmission (PMTCT) program is a comprehensive activity. The basic condition of the case is carried out because of the importance of health promotion and early detection in strategies for managing HIV, Syphilis, and Hepatitis B infections. This study aimed to analyzecontextual effect of community health service on the use of triple elimination service in pregnant women.Subjects and Method: This was a cross sectional study conducted at 25 community health centers in Sragen Regency, Central Java, from June to July 2019. A sample of 200 pregnant women was selected by stratified random sampling. The dependent variable was the use of triple elimination. The independent variables were age, perceived susceptibility, perceived seriousness, cues to action, attitude, motivation, occupation, income, and distance to health service. The data were collected by a set of questionnaire and analyzed by multilevel multiple logistic regression.Results: The use of triple elimination increased with age ?35 years (b=1.29; 95% CI=0.37 to 2.21; p=0.006), working outside the home (b=1.20; 95%CI=0.17 to 2.23; p=0.012), income by ?Rp 1,600,000 (b=1.52; 95% CI=0.54 to 2.50; p=0.002), perceived susceptibility (b=1.46; 95% CI=0.53 to 2.38; p=0.002), perceived seriousness (b=1.53; 95% CI=0.55 to 2.50; p=0.002), cues to action (b=1.30; 95% CI=0.30 to 2.30; p=0.010), attitude (b=1.10; 95% CI=0.02 to 2.18; p=0.046), and strong motivation (b=1.68; 95% CI=0.66 to 2.71; p=0.001). The use of triple elimination decreased by a distance ?5km (b=-1.36; 95% CI=-2.27 to -0.46; p= 0.003). Community health center had strong contextual effect on the use of triple elimination with ICC= 22.6%.Conclusion: The use of triple elimination increases with age ?35 years, working outside the home, income by ?Rp 1,600,000, perceived susceptibility, perceived seriousness, cues to action, attitude, and strong motivation. The use of triple elimination decreases by a distance ?5km. Community health center has strong contextual effect on the use of triple elimination.Keywords: triple elimination, Health Belief Model, Theory of Planned BehaviorCorrespondence: Prissy Verasita. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: prissyoppo@gmail.com. Mobile: +6285879-345269.Journal of Maternal and Child Health (2020), 5(1): 68-78https://doi.org/10.26911/thejmch.2020.05.01.08